Exploring intracellular anti-mycobacterium activity of lactoferricin-loaded niosomes: proteomics insights into Immunomodulation - Sirikwan Sangboonruang; Natthawat Semakul; Worrapan Poomanee; Thasang Thavanapong; Sittiruk Roytrakul; Sawanya Charoenlappanit; Siriwan Thaisakun; Jiaranai Khantipongse; Nathiprada Netirat; Apiwadee Tongsong; Usanee Wattananandkul; Sorasak Intorasoot; et al. (Scientific Reports)
Abstract Tuberculosis (TB) treatment faces significant challenges due to prolonged therapy and drug resistance, necessitating innovative anti-TB strategies. Thus, developing an innovative platform with effective anti-TB activity would offer more advantages. In this study, the pH-sensitive niosomal formulation of lactoferricin (Lfcin-Nio) was fabricated using a microfluidic system. The optimization of Lfcin-Nio formulation was statistically carried out based on the Central Composite Design (CCD). The desirable properties of Lfcin-Nio were achieved with a small particle size (171.68 ± 0.97 nm), a narrow polydispersity index; PDI (0.24 ± 0.002), an acceptable zeta potential; ZP (− 69.86 ± 0.64 mV), and high entrapment efficiency; %EE (75.59 ± 2.78%) with a prediction error of less than 5%. Lfcin-Nio demonstrated low cytotoxicity and stability for 28 days at room temperature and 4 °C. Lfcin-Nio also had a release profile in response to acidic pH, with approximately 50%, 70%, and 80% cumulative release at pH 7.4, 6.5, and 5.5, respectively, within the first 6 h. Notably, Lfcin-Nio exhibited enhanced anti-mycobacterial activity against both extracellular and intracellular Mycobacterium tuberculosis (Mtb), requiring a lower concentration for intracellular Mtb attenuation. Proteomic analysis revealed that Lfcin-Nio modulated immune response-related proteins, including complement C6 activation and suppression of inflammatory mediators. These findings suggest that Lfcin-Nio represents a promising anti-TB agent and further applies as a potential advancement in TB therapy.